Uji Efektivitas Pemberian Salep Ekstrak Etanol Daun Rimbang (Solanum torvum Swartz) Terhadap Penyembuhan Luka Sayat Pada Mencit Putih Jantan (Mus musculus) - Diana Novita; Helmice Afriyeni; Rosiana Rizal (Jurnal Sains Farmasi Dan Kesehatan, 2023)
Wounds are the loss or damage of part of the body's tissues that come from internal or external, resulting in several effects, namely bleeding, blood clotting, cell death, bacterial contamination and loss of some organ functions. This study aimed to examine the effect of giving ethanol extract ointment from mini-eggplant leaves (Solanum torvum Swartz) on wound healing in male white mice (Mus musculus). As many as 25 animals were induced with cuts and divided into 5 treatment groups, namely the positive control group (vaseline album), the comparison group (povidone iodine ointment 10%) and the treatment group with the ethanol extract of mini-eggplant leaf ointment (Solanum torvum Swartz) with a concentration of 2,5%, 5% and 10%. The ointment was applied according to the treatment group once a day for 14 days, measuring the length and width of the wound daily using a caliper to obtain the area of ​​the wound. The data obtained were then analyzed statistically using two-way ANOVA and continued with Duncan's test. The results of statistical analysis showed that the ethanol extract of mini-eggplant leaf (Solanum torvum Swartz) ointment had a significant effect on the healing of the wound area in male white mice (p<0.05). Mini-eggplant leaf ethanol extract ointment group had effectiveness on wound healing, which was indicated by the smaller the wound area in the test animals. The smallest area is shown at 5% ointment concentration, and the longer the time of administration of the ointment the smaller the incision area is shown on day 14.